Sensory Profiling of Mocaf (Modified Cassava Flour) Cookies with Substitution of Gomphrena globosa L. Powder Using the RATA (Rate-All-That-Apply) Method - Widyanti, Erika Deva; Anggreini, Riski Ayu; Putra, Andre Yusuf Trisna (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Gomphrena globosa L. flowers are edible flowers containing betacyanin and bioactive compounds that can contribute to the sensory attributes of food products, such as purple color and floral aroma. This study aimed to describe the sensory profile of mocaf-based cookies with Gomphrena globosa L. flower powder substitution (0%, 5%, 10%, 15%, and 20%) using the Rate-All-That-Apply (RATA) method. The evaluation was conducted by 70 untrained panelists using 22 sensory attributes, which were analyzed through the Kruskal-Wallis test and Principal Component Analysis (PCA). PCA results showed that sample F0 (100% mocaf) was dominant in sweet, caramel, fatty, and yellow color attributes; F1 (5%) in savory, crispy, light, and gritty attributes; F2 and F4 (10% and 20%) in firm, dry, bitter, burnt, throat irritation, and floral aroma attributes; whereas F3 (15%) was associated with floral, languid, ashy, roasted, purple, and brown color attributes